CAR-T cell therapies in autoimmune rheumatic diseases: a brief report on the clinical trial landscape, current status, and future perspectives - Xu, Xiao; Su, Su-Hua (Frontiers in Immunology, 2025)
Autoimmune rheumatic diseases (ARDs) are chronic inflammatory disorders where B cells play a key role. Traditional B-cell-targeted therapies have limitations, whereas CAR-T-cell therapy, which aims for a broader reset of the B-cell compartment by targeting B-cell surface markers such as CD19 or B-cell maturation antigen (BCMA), has unique advantages. Currently, most CAR-T cell trials for ARDs are in the early stages, with 64.29% (36/56 trials) of studies being phase I trials and only 7.14% (4/56 trials) progressing to phase II trials, primarily focusing on conditions, such as systemic lupus erythematosus (SLE) and lupus nephritis (LN). Geographically, clinical research is predominantly led by China (48% of trials [27/56 trials]) and the United States (34% of trials [19/56 trials]), although large-scale global collaborations remain limited, with only 3.6% (2/56 trials) of projects involving both U.S. and Chinese teams. Funding for these studies is driven primarily by non-leading pharmaceutical firms (75% [42/56 trials] of sponsors). Despite promising efficacy, e.g., CD19-targeted CAR-T cell therapy has induced significant clinical remission in refractory SLE patients, challenges remain, including high costs, complex production, and safety risks. Future progress requires expanding trials, optimizing CAR constructs, enhancing collaboration, and establishing safety monitoring networks, to promote the application of CAR-T cell therapy in ARDs and advance precision medicine.